Respuestas
Respuesta dada por:
1
a)
2(x-5)+4(x+1)=![\frac{3}{10} \frac{3}{10}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%7D%7B10%7D+)
2x-10+4x+4=![\frac{3}{10} \frac{3}{10}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%7D%7B10%7D+)
(2x-10+4x+4)*10=3
20x-100+40x+40=3
60x-60=3
60x=3+60
x=63:60
x=![\frac{150}{100} }simplificas \frac{150}{100} }simplificas](https://tex.z-dn.net/?f=+%5Cfrac%7B150%7D%7B100%7D+%7Dsimplificas)
x=![\frac{15}{10} }simplificas \frac{15}{10} }simplificas](https://tex.z-dn.net/?f=+%5Cfrac%7B15%7D%7B10%7D+%7Dsimplificas)
x=![\frac{3}{2} \frac{3}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%7D%7B2%7D+)
b)
6(1+2x)-2(x-3)=![\frac{1}{4} \frac{1}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B1%7D%7B4%7D+)
(6+12x-2x+6)*4=1
(12+10x)*4=1
48+40x=1
40x=1-48
x=
2(x-5)+4(x+1)=
2x-10+4x+4=
(2x-10+4x+4)*10=3
20x-100+40x+40=3
60x-60=3
60x=3+60
x=63:60
x=
x=
x=
b)
6(1+2x)-2(x-3)=
(6+12x-2x+6)*4=1
(12+10x)*4=1
48+40x=1
40x=1-48
x=
Preguntas similares
hace 6 años
hace 6 años
hace 9 años